PENDIDIKAN KESEHATAN PADA PASIEN DIABETES MELITUS TIPE 2 TENTANG MANFAAT BERAS MERAH DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Panjaitan, Ester Lita; Dewi, Rani Sartika; Khairani, Ade Irma (LPPM Institut Pendidikan Nusantara Global, 2023)
Diabetes Mellitus is a disease that disrupts the metabolic system which is characterized by increased blood glucose levels caused by insulin retention. Health education is a form of independent action to help clients, both individuals, groups and communities, overcome health problems through learning activities. Brown rice is a part of the herbal plant that contains flavonoid compounds which have anti-diabetic abilities which reduce blood glucose. Objective: The aim of the research is to provide health education to type two diabetes mellitus patients about the benefits of brown rice. Research Method: The research method is a case study with a housing approach. Results: The results obtained in cases one and two were obtained from data on the third day after implementation, the cause of the problem of lack of knowledge was resolved. Conclusion: The results of the study showed that both clients experienced the same problem, namely a lack of knowledge and carried out the same killings for three days and the results were obtained from providing health education about the benefits of effective brown rice given to patients with type two diabetes mellitus. Suggestion: Research recommendations hope that clients will have the desire to change their diet and lifestyle.